Valoración del contenido nutricional del pasto Saboya (Panicum máximum jacq) con diferentes niveles de fertilización y época de corte en la zona de Babahoyo - Provincia de Los Ríos - Malave Maldonado, Wilson Wladimir (2019)
This research work was carried out on the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo-Montalvo road, between the months of June, July, August and September of 2019. Its objective was to assess the nutritional content of the Savoya grass (Panicum Máximum Jacq.), With different levels of fertilization and cutting time. The genetic material used was the unimproved Savoya grass present in the FACIAG grounds. The treatments were fertilization levels of 200 and 250 kg/ha and the cuts at 30 and 50 days after the equalization cut. Deductive, inductive and experimental methods were used. Analysis techniques were used to estimate, arithmetic mean, range of variation, standard deviation and coefficient of variation. The variables evaluated were; yield of fresh matter (Kg/m2), percentage of dry matter (%DM) plant height (cm) and the nutritional value of the grass at 30 and 50 days after the equalization cut (%). After analyzing the results, it was concluded that: In the treatment of 250 kg/ha of fertilizer with a cutting day of 50 the yield of green matter was 2.35 kg/m2, while 30 days after cutting and by fertilizing 200 kg/ha a result of 2.03 kg/m2 was obtained. The highest percentage of dry matter (% DM) was obtained at the age of 50 days with fertilization of 250 kg/ha with (27.84% DM). While the lowest value was obtained at 30 days of cutting with a fertilization of 200 kg/ha with a value of (24.67% DM) and the treatment that had the highest height was that of 200 kg/ha with a cutting day of 50 with a value of 1.94cm. and the one of smaller size was the one of the treatment of 250 kg/ha at 30 days of the cut with a height of 0.99cm. The percentages of minerals are influenced by the levels of fertilization applied to the soil and the edafoclimatic conditions present in the area. For this we can say that in the results obtained from the cut made at 30 days we found a higher concentration of minerals present in the plant, compared to the results obtained from the cut made at 50 days